2019
DOI: 10.1186/s13041-018-0417-0
|View full text |Cite
|
Sign up to set email alerts
|

The peacefulness gene promotes aggression in Drosophila

Abstract: Natural aggressiveness is commonly observed in all animal species, and is displayed frequently when animals compete for food, territory and mating. Aggression is an innate behaviour, and is influenced by both environmental and genetic factors. However, the genetics of aggression remains largely unclear. In this study, we identify the peacefulness (pfs) gene as a novel player in the control of male-male aggression in Drosophila. Mutations in pfs decreased intermale aggressiveness, but did not affect locomotor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 49 publications
2
40
0
Order By: Relevance
“…whose expression is likely evolving under directional selection) include the X-linked gene cinnamon (FBgn0000316, ratio_male = 86.15, ratio_female = 302.26). Cinnamon , which is involved in the biosynthesis of the molybdenum cofactor and inter-male aggression (Kamdar et al 1994; Ramin et al 2019), has changed sex-bias in its recent evolutionary history: it has female-biased expression in both D. melanogaster and D. simulans and male-biased expression in D. yakuba .…”
Section: Resultsmentioning
confidence: 99%
“…whose expression is likely evolving under directional selection) include the X-linked gene cinnamon (FBgn0000316, ratio_male = 86.15, ratio_female = 302.26). Cinnamon , which is involved in the biosynthesis of the molybdenum cofactor and inter-male aggression (Kamdar et al 1994; Ramin et al 2019), has changed sex-bias in its recent evolutionary history: it has female-biased expression in both D. melanogaster and D. simulans and male-biased expression in D. yakuba .…”
Section: Resultsmentioning
confidence: 99%
“…From a mechanistic perspective, external factors could differentially affect levels of oxidative stress. It is well documented, for example, that caloric restriction (Ungvari et al, 2008) and even social interaction (Ruan and Wu, 2008) can reduce accumulation of reactive oxygen species (ROS) whereas aggressive encounters may promote ROS production (Ramin et al, 2019). A recent and emerging concept in the Drosophila sleep field is that sleep is affected by levels of oxidative stress, and sleep deprivation can accelerate accumulation of ROS (Hill et al, 2018; Kempf et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The integration of sensory input and the integration of this input with memory processes is key to our fitness and known to develop well into adulthood 64 . Exposure to serotonin altering medication during development has been related to differences in neuronal and behavioural levels 16 28 . In this study we found brain-wide differences in functional activity during adolescence and adulthood as a consequence of perinatal SSRI exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Rodent models fill this gap, giving us the opportunity to closely investigate the consequences of developmental SSRI exposure. These preclinical studies have suggested differences in social behaviour, learning and memory, anxiety and sensory functions, alterations in neuronal organization, differences in hippocampal neurogenesis and epigenetic changes after SSRI exposure during pregnancy and the early postnatal phase 16 28 .…”
Section: Introductionmentioning
confidence: 99%